(untitled) (Indonesian Journal of Science and Technology, 2025)
Green polybags offer an eco-friendly alternative to conventional plastic polybags, which pose environmental concerns due to their slow decomposition. This study explores the optimal composition of empty fruit bunches (EFB), sawdust waste (SW), and natural rubber latex (NRL) to develop biodegradable green polybags that function as both containers and planting media. The best formulation—EFB 140 g, SW 40 g, and NRL 60 g—exhibited a density of 0.6762 g/cm³, moisture content of 6.71%, water absorption of 45.28%, and biodegradation rate of 29.91%. Seedlings grew successfully in this medium, demonstrating its effectiveness. FTIR analysis confirmed the presence of hydroxyl, carbonyl, aliphatic, and ester groups, while SEM-EDX analysis indicated high carbon and oxygen content in EFB and SW. The results suggest that green polybags are a sustainable and biodegradable alternative, promoting environmental conservation and plant growth.